Adebrelimab plus chemotherapy vs. chemotherapy for treatment of extensive-stage small-cell lung cancer from the US and Chinese healthcare sector perspectives: a cost-effectiveness analysis to inform drug pricing - Gan, Yena; Shi, Fenghao; Zhu, He; Han, Sheng; Li, Duoduo (Frontiers in Pharmacology, 2023)
Purpose: The aim of this study was to evaluate the cost-effectiveness of a recently approved first-line therapy (adebrelimab plus chemotherapy vs. chemotherapy alone) for patients with extensive-stage small-cell lung cancer (ES-SCLC) in the US and China, and to estimate the reasonable range of adebrelimab price from the decision-makers. Methods: Several partitioned survival models were built to compare the cost and effectiveness of adebrelimab plus chemotherapy vs. chemotherapy alone over a 10-year time horizon. Clinical efficacy and safety data were extracted from the CAPSTONE-1 trial. Costs and utilities were obtained from previously published studies. Sensitivity, scenario and subgroup analyses were performed to explore the uncertainty of the model outcomes. Price simulation was conducted at three thresholds of willingness-to-pay (WTP), including WTP of $100,000 in the US and of $37,422 in China, 0.5WTP of $50,000 in the US and of $18,711 in China, and 1.5WTP of 150,000 in the US and of $56,133 in China. Findings: Base-case analysis at $1382.82/600 mg of adebrelimab price indicated that adebrelimab plus chemotherapy would be cost-effective in the US at the WTP threshold of $100,000, but not in China at the WTP threshold of $37,422. If PAP was taken into account, the regimen would be cost-effective in China at the given WTP. The results of price simulation indicated that adebrelimab plus chemotherapy was completely favored in the US if adebrelimab price was less than $8894.98/600 mg (total quality-adjusted life years [QALYs] were calculated with progression-based utility [PB-utility]) or $8912.51/600 mg (total QALYs were calculated with time-to-death utility [TTD-utility]) at the WTP threshold of $100,000; if adebrelimab price was reduced by at least $202.03/600 mg (total QALYs were calculated with PB-utility) or $103.06/600 mg (total QALYs were calculated with TTD-utility), the regimen was also cost-effective in China without PAP at the WTP threshold of $37,422. The above results were stable in the sensitivity analyses. Subgroup analysis found that the subgroup with better survival benefits tended to have a higher probability of cost-effectiveness, which was also associated with adebrelimab price. Implications: First-line adebrelimab plus chemotherapy represented a dominant treatment strategy comparing with chemotherapy alone in the US and also did in China with PAP at $1382.82/600 mg of adebrelimab price. Decision-makers could benefit from pricing strategy provided by this study in making optimal decisions. More evidences were needed to verify and improve the results.